Nutritional characteristics and development factors of U.S. prison menus - Bain, Laura (Kansas State University, 2023)
Nutrition-related health disparities plague prisons in the United States. Taxpayers fund the rising healthcare costs for the incarcerated. Unregulated inadequate prison menus may contribute to non-communicable chronic health conditions in a vulnerable population. Correctional registered dietitian nutritionists (RDNs) support menu development in a variety of ways including advocating for nutritionally beneficial menu choices. The purpose of this exploratory research was to assess nutrition offerings provided by prison menus as well as gain insight on current factors influencing menu nutrition. Research methods included a two-phase approach to data collection. Records requests to obtain master menus and associated nutrition analyses were submitted to all United States departments of corrections; a total of 33 states provided documents for analysis. Researchers found that prisons serve gendered menus to the general population, and 52.9% of gendered menus provide the same offerings to both males and females. Female overall nutrition needs are lower than males, therefore, 52.9% of gendered menus provide excess calories, and saturated fat to females. Sodium is served in excess to both males and females. Fruit and vegetable servings on all gendered menus fell short of the Dietary Guidelines for Americans recommendations. The average prison menu inappropriately estimates calories, macronutrients, sodium, and other micronutrients in a one-size-fits-all menu development method without considering gender, age, and physical activity. A survey was developed and distributed to obtain correctional nutrition professional’s perspective on factors influencing menu nutrition. Researchers attempted to contact dietitians in all departments of corrections as each department must contract RDN services for menu approval to achieve accreditation. In total, researchers invited 34 corrections nutrition professionals to participate in and 24 completed the survey representing 20 state prison systems. Survey response data indicated that eight departments of corrections contract with outside RDNs who were less accessible to researchers. Menus approved by contract dietitians provided less fruit and vegetable servings. Nutrition guidelines recommend consuming no more than half of fruit servings as fruit juice; states whose menus served the highest proportion of fruit juice contracted for RDN services, all of which exceed guidelines. Eighteen states menus include a fortified beverage to supplement menu item nutrient offerings. Ten of the 18 states also contract for RDN services, and nine out of 10 contract menus including fortified beverages serve less than the recommended amount of fruit servings. Findings from this research provide opportunities for further investigation into corrections menus. Nutrition offerings from prisons including fortified beverages and prison menus offered by contract services will provide additional insight on menu adequacy. Religious menus are offered to general prison populations and understudied. This work supports corrections-specific guideline development which will be supported by additional research in this vital area.
Keywords: Prison menu; Corrections menu; Prison nutrition; Corrections nutrition; Prison menu development; Corrections menu development; Prison dietitian; Corrections dietitian